Acyldepsipeptide Analogs Dysregulate Human Mitochondrial ClpP Protease Activity and Cause Apoptotic Cell Death. Issue 8 (16th August 2018) - Wong, Keith S.; Mabanglo, Mark F.; Seraphim, Thiago V.; Mollica, Antonio; Mao, Yu-Qian; Rizzolo, Kamran; Leung, Elisa; Moutaoufik, Mohamed T.; Hoell, Larissa; Phanse, Sadhna; Goodreid, Jordan; Barbosa, Leandro R.S.; et al.
Summary: Acyldepsipeptides (ADEPs) are potential antibiotics that dysregulate the activity of the highly conserved tetradecameric bacterial ClpP protease, leading to bacterial cell death. Here, we identified ADEP analogs that are potent dysregulators of the human mitochondrial ClpP (HsClpP). These ADEPs interact tightly with HsClpP, causing the protease to non-specifically degrade model substrates. Dysregulation of HsClpP activity by ADEP was found to induce cytotoxic effects via activation of the intrinsic, caspase-dependent apoptosis. ADEP-HsClpP co-crystal structure was solved for one of the analogs revealing a highly complementary binding interface formed by two HsClpP neighboring subunits but, unexpectedly, with HsClpP in the compact conformation. Given that HsClpP is highly expressed in multiple cancers and has important roles in cell metastasis, our findings suggest a therapeutic potential for ADEPs in cancer treatment. Graphical Abstract: Highlights: Acyldepsipeptides dysregulate the activity of human mitochondrial ClpP protease Dysregulation of mitochondrial ClpP by ADEPs causes apoptotic cell death Co-crystal structure of HsClpP with ADEP reveals another conformation of the protease Results suggest a therapeutic potential for ADEPs in cancer treatment Abstract : Acyldepsipeptides (ADEPs) are potential antibiotics that dysregulate the activity of the highly conserved bacterial ClpP protease. We identified ADEP analogs that are potent dysregulators of the human mitochondrial ClpP (HsClpP). The compounds were found to cause apoptotic cell death. The ADEP-HsClpP co-crystal structure revealed, unexpectedly, HsClpP in the compact conformation.